Formação de treinadores da elite do futebol masculino brasileiro - Souza, Leonardo Sampaio de (Universidade Federal de São Carlos, 2024)
The top tier soccer coaches of the male brazilian teams have a plethora of specific knowledge to act in thein field, such knowledge was acquired through study and practical experiences. Those studies are the focus of this monograph, conducting a review of previous information and, then, analyze the formation of the coaches that worked in the clubs of the A Series in the Brazilian Male Soccer Championship 2023. Therefore, the research objective consists in interpret and analyze the formative process of the soccer coaches that worked in said championship. We used qualitative methodological bases, conducting documental and bibliographical research, respecting the obtained information using the documental technique to expose collected data in the most evident way. Then we conducted the analysis, categorizing and adding the obtained results with the courses from the considered institutions, looking for the general characterístics surrounding the coach profession in Brazil. The CONMEBOL and UEFA confederations have established minimal requirements to federations and institutions within each country, qualifying their soccer coaches in different levels. These courses aim to elevate the technical and tactical patterns of playing, and even with the standardization of courses there are differences in cultural formation regarding styles and approaches from coaches. That is due to the way they played and learned throughout their lives, making them unique and different in the plethora of technical and tactical knowledge passed on the elite brazilian soccer players, creating a diversity of technical and tactical applications that are seen within the field.
Training elite coaches in Brazilian men's football
Formación de entrenadores de élite en el fútbol masculino brasileño
Keywords: Futebol; Formação de treinadores; Treinadores de futebol; CIENCIAS DA SAUDE::EDUCACAO FISICA